Practical guide to Latin America including Mexico, Central America, The West Indies and South America. Preparation, cost, routes sight-seeing (1912)
This little homily contains for the experienced traveller the advice to refrain from odious comparisons between the unsettled conditions and methods of the new world and the established and more advanced ones in older civilizations. To the novice a few words of helpful suggestion may not come amiss, and may show him how to see the advantages of the new and to endure the absence of what he is used to at home.